APPLICATION OF QUANTUM LEARNING TO ENHANCE STUDENT LEARNING AND ACHIEVEMENT OF SELF-SUSTAINABILITY - Samsiah Samsiah; Turdjai Turdjai (DIADIK, 2019)
The purpose of describing the application of Quantum Learning l to the independence in improving of students study in economic subjects in SMA N 1 Lebong. Research methods the research was quasi experiment and class actions. The subject class IPS 1 X 1 as a class action for applying Quantum learning model and the number of students 28. The technique of data collection for Research Action class (PTK) uses observation sheets  to observe the independence and test instruments to measure the achievement of the objectives of learning ability, and to test instrument use quasi experiment. Data analysis wa frs done by the average (class) and t- test. The results of this research indicate: 1) the applicability of Quantum Learning Teaching model can increase the independence of the student learning Indonesian on subjects of Class XI IPS in SMA N 1 Lebong; 2 application of Quantum learning model) Teaching can improve student learning and achievement into his own motivation for students in the following learning materials; 3 application of Quantum learning model) Teaching is effective in improving student learning achievement in the economic lesson the class XI IPS in SMA N 1 Lebong.